KOHESI GRAMATIKAL DAN LEKSIKAL PADA PENGGALAN NOVEL “KEKUATAN EKOR BIRU NATAGA” DALAM BUKU AJAR BAHASA INDONESIA KELAS 7 - Mujahid Taha; Gusnawaty Gusnawaty; M. Syafri Badaruddin (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This study describes the form of grammatical and lexical cohesion markers between sentences contained in the fragment of the novel Strength of the Blue Dragon in the Class 7 Indonesian Language Textbook. This research is a qualitative descriptive study with data in the form of linguistic aspects, especially internal language studies, grammatical cohesion markers and lexical. The results showed that grammatical and lexical cohesion elements were found including, grammatical: additional or additive conjunctions, namely in the word and and di-serta-i, and also, sequence or sequence conjunctions in the past word, and adverb conjunctions of place in the word with. Lexical: repetition with full repetition of a noun (personal name; Nataga); synonyms in the form of nouns (personal names; Tana Modo and Tana Air); antonyms in the form of verbs, namely the word fall and ready to attack; collocation in the form of nouns and adjectives, namely words that highlight eyes, are red, and are full of anger; hyponyms in the form of nouns (animals), namely the words ants, termites, and mice (animals); and equivalence in the form of verbs and nouns, namely the words siege and siege.